Duration of Hemodialysis and its Impact on Quality of Life: Hemodialysis and its Impact on Quality of Life - Akram, Bushra; Ahmad, Hafiz Shafique; Akhtar, Muhammad Tahsin; Bilal, Ahmad; Iqbal, Khizra (Pakistan Journal of Health Sciences, 2023)
One of the main treatments for people with end-stage renal illness is hemodialysis. In managing patients with hemodialysis-dependent chronic kidney disease, quality of life is crucial. Objective: To determine duration of hemodialysis and its impact on Quality of Life. Methods: A descriptive, correlational research design was used to investigate the quality-of-life patients with hemodialysis. Purposive sampling technique was used in selection of the participants. This study was conducted at the Nishtar Hospital's Renal Dialysis Unit, a teaching hospital affiliated with Nishtar Medical University, Multan. The sample consisted of 50 patients (Male-32, Female-18) on Hemodialysis. World Health Organization Quality of Life BREF (WHOQOL, BREF) Urdu version was administered to assess the quality of life due to hemodialysis treatment. Results: Results showed that out of 50 subjects, majority of patients 32 (64%) were Male, 17 (34%) were about 31-40 years age group, 11(22%) were on hemodialysis treatment from 5 years. In quality of life, 38.2% patient’s physical domain more affected in 2 years of hemodialysis, 31.4% were affected in psychological domain in less than 03 months, 23.4% affected in social domain after 5 years of dialysis and 39% environmental domain disturbed in 4 years of dialysis. Conclusions: It was concluded that Hemodialysis strong effect on quality of life of the patients and its duration and prolonged hemodialysis also impact on patients’ social relationships, psychological domain, physical health and environment domain.